B cell/stromal cell crosstalk in health, disease, and treatment: Follicular lymphoma as a paradigm. Issue 1 (31st May 2021) - Lamaison, Claire; Tarte, Karin
Abstract: Stromal cells organize specific anatomic compartments within bone marrow (BM) and secondary lymphoid organs where they finely regulate the behavior of mature normal B cells. In particular, lymphoid stromal cells (LSCs) form a phenotypically heterogeneous compartment including various cell subsets variably supporting B‐cell survival, activation, proliferation, and differentiation. In turn, activated B cells trigger in‐depth remodeling of LSC networks within lymph nodes (LN) and BM. Follicular lymphoma (FL) is one of the best paradigms of a B‐cell neoplasia depending on a specific tumor microenvironment (TME), including cancer‐associated fibroblasts (CAFs) emerging from the reprogramming of LN LSCs or poorly characterized local BM precursors. FL‐CAFs support directly malignant B‐cell growth and orchestrate FL permissive cell niche by contributing, through a bidirectional crosstalk, to the recruitment and polarization of immune TME subsets. Recent studies have highlighted a previously unexpected level of heterogeneity of both FL B cells and FL TME, underlined by FL‐CAF plasticity. A better understanding of the signaling pathways, molecular mechanisms, and kinetic of stromal cell remodeling in FL would be useful to delineate new predictive markers and new therapeutic approaches in this still fatal malignancy.